Intimate Partner Violence Against Women in Kohalpur Municipality of Banke District, Nepal - Sharma, Bhagawoti (Journal of Health Promotion, 2020)
Intimate partner violence (IPV) is abuse that occurs in a close relationship. The main purpose of this study is to determine the forms and risk factors associated with violence as well as the effect of demographic elements on IPV. The population of this study was all the women of the reproductive age group in Ward No. 7 of Kohalpur Municipality Banke district, Nepal. For this study 151 married women aged 15-49 years were selected from Kohalpur municipality by using. convenience sampling method. Data were collected through the interview schedule and attitude scale. The researcher has found that 33.11 percent respondents strongly agreed that they were afraid of their husbands and 53.64 percent respondents strongly agreed that their husbands physical forced to have sex. Likewise, 17.21 percent respondents pointed IPV is due to lack of education and 55.62 percent due to gambling and drinking behaviors of their husbands. Similarly, 6.62 percent respondents pointed out that it is due to fewer dowry system. IPV, a serious problem, has long-lasting effects on individuals, families and society also. So this has to be prevented. To reduce the proportion of IPV, healthy, respectful, understanding and an appropriate environment has to be promoted instead of violent relationships.